Analisis Pemantauan Dosis Efektif Jaringan Paru-Paru pada Pekerja Radiasi Menggunakan Thermoluminescent Dosimeter (TLD) di RSUD A.W. Sjahranie Samarinda - Erlin Rappan; Rahmawati Munir; Erlinda Ratnasari Putri (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2024)
Thermoluminescent Dosimeter (TLD) is a personal dosimeter to measure radiation exposure which can capture and store radiation energies. It hits them and emits them in the form of light when heated. TLD aims to measure radiation exposure received by radiation workers. The purpose of this study was to determine the effective dose value of lung tissue at the Radiology, Radiotherapy, and Nuclear Medicine Installations in 2018 until 2021 at A.W. Sjahranie Samarinda Hospital. Data processing in this study was carried out using quantitative analysis techniques, i.e., descriptive statistics. This analysis technique used secondary data obtained from the results of recapitulation of absorbed dose values in Radiology, Radiotherapy, and Nuclear Medicine Installations. Data processing was performed by multiplying the equivalent dose values by the lung tissue weight factor. The results of these calculations are visualized in the form of graphs based on the effective lung doses for years and types of installation. Based on this study, in general, the highest to lowest effective dose values for lung tissue are from the Radiotherapy, the Nuclear Medicine, and the Radiology Installations. It matches theoretically in various references.